TRAINING OF FUTURE EDUCATORS TO WORK WITH GIFTED CHILDREN IN THE CONTEXT OF THE NEW EDITION OF THE BASIC COMPONENT OF PRE-SCHOOL EDUCATION OF UKRAINE - Lazarovych, Nadiia; Matsuk, Lyudmila; Zakharasevych, Nataliia (Mountain School of Ukrainian Carpaty, 2021)
In the article the peculiarities of training of future educators in HEE to work with gifted children are analyzed. The main conditions for the formation of a graduate of the specialty "Preschool Education" of the first (bachelor's) educational level are described. The importance of educators' training to work with gifted preschoolers has been experimentally proven by practicing teachers of Ivano-Frankivsk. The essence of the concept "giftedness" in psychological and pedagogical research is theoretically analyzed. Emphasis is placed on the main tasks of the organization of the educational process in school with gifted children in accordance with the updated Basic Component of Pre-school Education in Ukraine (2021). The specifics of formation of professional competencies of a preschool education specialist in the Standard of Higher Education of Ukraine of the first educational (bachelor's) level are analyzed. The main conditions for ensuring future educators’ professional competence considering educational components of the educational program are described. The importance of creating an educational model of the formation of graduate qualities necessary for work on the development of children's talents is substantiated. The importance and interdependence of planning and introduction of educational components is proved, taking into account the formation of life competencies of children, assigned in the Basic Component of Pre-school Education of Ukraine. The study implied a set of methods: analysis and synthesis, induction and deduction, comparison, systems analysis. The use of such a wide methodological range made it possible to structure the theoretical material of the problem under study with the help of visual elements.